Indice neutrófilo/linfocito elevado como predictor de mortalidad intrahospitalaria en pacientes no fumadores con exacerbación aguda de enfermedad pulmonar obstructiva crónica - Calzado Lama, Jaime Jeinson (2019)
BACKGROUND: Acute exacerbation of COPD is considered one of the main causes of hospitalization and contributes significantly to mortality among patients with COPD. Neutrophilia, an indicator of inflammation associated with lymphocytopenia, an indicator of decreased immune competence, leads to postulate that the neutrophil / lymphocyte index (INL) would reflect the severity and prognosis. OBJECTIVE: To identify whether the elevated neutrophil / lymphocyte index is a predictor of in-hospital mortality in nonsmokers with acute exacerbation of chronic obstructive pulmonary disease. MATERIAL AND METHOD: An observational analytical, prospective cohort study aimed at non-smoking patients with acute exacerbation of chronic obstructive pulmonary disease, with a neutrophil / peripheral blood lymphocyte index greater than 4, and whose clinical records include data corresponding to the mortality. ANALYSIS OF RESULTS: The record in the data collection sheets to be processed using the statistical package SPSS V 20.